PTH-102 Stat2 is a key inflammatory molecule in human non-alcoholic fatty liver disease and murine liver injury. (22nd June 2015) - Alazawi, W; Heath, H; Petts, G; Kudu, H; Feakins, R; O'Brien, A; Goldin, R; Foster, GR
Abstract : Introduction: In patients with non-alcoholic fatty liver disease (NAFLD), liver inflammation is a key histological feature that distinguishes benign simple steatosis from progressive non-alcoholic steatohepatitis (NASH). The mechanisms that underlie this process are poorly understood. We recently showed that Stat2 plays a pivotal role in acute inflammation, independent of its role as an interferon mediator. The aim of the current study is to test the hypothesis that STAT2 is associated with hepatic inflammation in patients with NASH and in a murine model of liver injury. Method: Expression of (phosphorylated, p) STAT2 and STAT1 was assessed by immunohistochemistry in anonymised sections of archived liver tissue taken from consenting patients with NASH at The Royal London and St Mary's Hospitals (London, UK). STAT2 -/- and WT mice were injected with incremental doses of carbon tetrachloride (CCl4) for 4 or 6 weeks. Serum and liver tissue were harvested 24 or 72hrs after the last injection. Immunohistochemistry for activated stellate cells (anti-alpha smooth muscle actin, aSMA) and macrophage/Kupfer cells (anti-F4/80) was performed. Results: Tissue from 62 patients was examined. Hepatocyte nuclear expression in NASH liver tissue was significantly greater for STAT1 (74% vs 10%, p < 0.0001) and STAT2 (98% vs 35%, p < 0.0001) compared to normal liver. There was a significant correlation between STAT1 expression (r = 0.6, p = 0.02), but not STAT2 and the NAFLD activity score (NAS). Animal models confirm that Stat 2 plays a role in liver inflammation – Stat2 -/- mice were protected from CCl4 -mediated liver injury with reduced serum alanine aminotransferase (ALT, 2165 vs 1090 iU/ml, p = 0.03), inflammation and necrosis histologically and fibrosis (Picrosirius red staining). There were no significant differences in the number of aSMA or F4/80-positive cells between WT and Stat2 -/- mice. Conclusion: These data identify a novel role for STAT2 in the development of liver disease, with expression of STAT1 and STAT2 relating to disease grade. The protection afforded by Stat2 loss in murine models is unrelated to macrophage and stellate cell activation, and we hypothesise that the mechanism of protection is therefore reduced production of Stat2-mediated cytokine production. Disclosure of interest: None Declared.